Ultrasound Guided Trigger Point Injection and Sciatic Nerve Hydrodissection for Atypical Piriformis Syndrome: A Case Report - Pun, Iswar Kumar; Amatya, Shirish Prasad; Moktan, Sushila Lama; Lamichhane, Suraj; Pun, Insha (Medical Journal of Armed Police Force Nepal, 2026)
Introduction : Chronic low back pain is a common complaint and is often attributed to lumbar disc disease. Less recognized causes, such as piriformis syndrome, can be overlooked, especially when routine tests and imaging are inconclusive. Early accurate diagnosis and targeted therapy are essential for effective pain relief.Case presentation: A 39-year-old male experienced six years of atraumatic low back pain radiating to his left leg and sole, worsening over 10 days and aggravated by prolonged sitting or standing. Examination revealed left piriformis tenderness but negative provocative tests, with minimal sensory deficit in the left L5 dermatome. Imaging showed a lumbarisation of sacral vertebra and L4–L5 disc bulge with bilateral lateral recess narrowing causing indentation of L4 exiting nerve root, which did not fully explain his symptoms. He had previously tried physiotherapy, oral steroids, neuromodulators, and analgesics without relief. Ultrasound-guided piriformis trigger point injection and sciatic nerve hydrodissection provided rapid and significant pain relief, confirming the piriformis as the primary pain source.Conclusions: This case highlights the diagnostic and therapeutic utility of ultrasound-guided, safe, and minimally invasive interventions in atypical piriformis syndrome refractory to conservative management.